A STUDY ON MIND MAPPING TECHNIQUE IN IMPROVING STUDENTS’ READING COMPREHENSION - Desri Desri; Darmawan Darmawan; Wahyudin Wahyudin; Mashuri Mashuri (Tadulako University, 2026)
This study seeks to examine how effective the Mind Mapping technique is in improving students’ reading comprehension by employing a qualitative library research approach. The data were gathered from five earlier studies conducted between 2018 and 2023 that explored the use of Mind Mapping in reading instruction. These studies applied a range of research designs, including Classroom Action Research, pre-experimental, and quasi-experimental approaches. The data were analyzed through content analysis in order to explore recurring patterns, as well as similarities and differences across the findings. The findings of this study suggest that the Mind Mapping technique contributes positively and significantly to students’ reading comprehension. The results demonstrate steady improvement in students’ reading performance, a higher proportion of students meeting the minimum mastery standards, and increased engagement throughout the learning activities. Mind Mapping enables students to structure and represent information visually, which supports their understanding of key ideas, supporting details, and the connections within a text. Furthermore, the technique encourages active participation, cooperative learning, and the development of higher-level thinking abilities, such as interpreting and assessing information. The study also indicates that the effectiveness of Mind Mapping largely depends on how well teachers facilitate and integrate the technique into classroom practices. In general, Mind Mapping can be considered a practical and efficient instructional strategy for improving reading comprehension. Therefore, it is advisable for teachers to incorporate this technique into their teaching in order to foster a more engaging and meaningful learning environment.